2018
DOI: 10.1093/ibd/izy294
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Anti-TNF-Alpha Therapy During Pregnancy on Long-term Outcome of Exposed Children: A Controlled, Multicenter Observation

Abstract: Background: Evidence of the impact of in utero exposure to anti-tumor necrosis factor (TNF)-alpha on long-term childhood development is limited. The aim was to assess the impact of in utero exposure to anti-TNF-alpha due to mothers' inflammatory bowel disease (IBD) on longterm postnatal development of exposed children. Methods: We included consecutive children (≥12 months of age) born to mothers with IBD (2007-2016) treated with anti-TNF-alpha during pregnancy in 3 centers in the Czech Republic. A control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 13 publications
3
53
0
2
Order By: Relevance
“…No adverse events after vaccination were reported. The rate of vaccination in our cohort is comparable to previous cohorts of TNFE children, though the administration rate of live attenuated vaccines was lower in our cohort …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…No adverse events after vaccination were reported. The rate of vaccination in our cohort is comparable to previous cohorts of TNFE children, though the administration rate of live attenuated vaccines was lower in our cohort …”
Section: Discussionsupporting
confidence: 79%
“…The rate of vaccination in our cohort is comparable to previous cohorts of TNFE children, though the administration rate of live attenuated vaccines was lower in our cohort. [20][21][22][23] Overall, the risk of adverse pregnancy outcome was similar within the three groups. Furthermore, the risk of congenital anomalies was low, and comparable among the three groups.…”
Section: Discussionmentioning
confidence: 82%
“…The median ratio of infant to maternal drug concentration at birth was 1.97 (95% CI 1.50-2.43) in 44 patients (18 patients and 26 patients received last infusion before and after the 30th GW, respectively) [136]. In another study the median concentration was 7.8 μg/mL in patients who used infliximab until the 18th-36th weeks of gestation [51].…”
Section: Infliximabmentioning
confidence: 95%
“…The follow-up of children is one of the longest compared to previously published cohorts. [4][5][6][7][8][9] Although the study demonstrated slightly in- Somewhat conflicting, however, the impact of combined immunosuppressive treatment still remains. While two previous studies reported increased risk of infections in children exposed to combination of anti-TNF and thiopurines, others did not find any risk.…”
Section: N V I T E D E D I T O R I a L Editorial: Safety Of Prenatamentioning
confidence: 99%
“…While two previous studies reported increased risk of infections in children exposed to combination of anti-TNF and thiopurines, others did not find any risk. [4][5][6][7][8][9] This discrepancy could be related to different definitions of infectious complication used or other confounders as discussed above.…”
Section: N V I T E D E D I T O R I a L Editorial: Safety Of Prenatamentioning
confidence: 99%